Bisnis Keluarga - Anis Fitria (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This article presents how the factors affecting family owned and managed businesses are examined and related to how the business literature develops. In addition, it discusses important patterns in the current literature and new directions regarding family business for future study. This study identifies the main research topics and methodical approaches in a systematic literature review to understand the family business. Insights about behind the historic changes and current directions and trends of family business literature are also identified. The findings of this study argue that the main cause of challenges in running a family business is sourced from managing the relationship between family interests and business interests. The key success factors are strong leadership and building a culture that accepts continuous change.